Analysis of Murabahah Contracts in Financing and Their Contribution to SDGs in Sharia Financial Institutions - Haidar Ali; Muthoifin; Mariam Elbanna (Universitas Muhammadiyah Surakarta, 2025)
Objective: The purpose of this study is to analyze the implementation of murabahah contracts in Islamic financial institutions, focusing on the implementation mechanism, the application of sharia principles, and the challenges faced in the transaction process. This study also explores how the implementation of murabahah contracts contributes to the achievement of several Sustainable Development Goals (SDGs), particularly in promoting inclusive economic growth (SDG 8), strengthening financial institutions (SDG 16), and supporting ethical consumption and production patterns (SDG 12). Theoretical framework: The theoretical framework used in this study is based on Islamic economic principles and sharia provisions related to murabahah contracts, including the important role of cooperation with third parties such as suppliers. It is contextualized with the SDGs framework to assess the alignment between Islamic finance practices and global development goals. Literature review: A literature review is conducted through a literacy study that collects various views and previous findings regarding the practice of murabahah contracts in Islamic financial institutions. The review also includes discussions on how Islamic finance can serve as a tool for achieving SDGs, particularly in enhancing financial inclusion and responsible financing. Methods: The method used is a qualitative approach with literature studies as the main data collection technique. Results: The results of the study show that even though the murabahah contract is theoretically in line with sharia principles, in practice there are still various obstacles such as unclear costs and uncertainty between related parties. In addition, cooperation with suppliers as third parties is considered important for smooth transactions but requires strict supervision to remain in accordance with sharia rules. Effective murabahah implementation supports SDGs by ensuring equitable access to financing and enhancing trust in Islamic financial systems. Implications: The implication of this study is the need to increase sharia efficiency and compliance in the implementation of murabahah contracts, especially in the aspects of transparency and supervision of third parties. These improvements are crucial to align Islamic financial practices with SDGs, particularly in ensuring justice, accountability, and sustainable economic systems. Novelty: The novelty of this study lies in a comprehensive discussion of the strategic role of cooperation with suppliers in the implementation of murabahah contracts, which has not been studied in depth in previous studies.